Social filters shaping student responses to teacher feedback in the secondary drama classroom. Issue 1 (2nd January 2019) - Hogan, Sharon Leanne
ABSTRACT: Little is known about how secondary drama students identify or utilise teacher feedback. This article presents findings from a study exploring how drama students describe their experiences of teacher feedback and how, or if, they apply this feedback to enhance their learning. Data collection and analysis focused on students' experiences of teacher feedback occurring in three secondary drama classrooms in Queensland, Australia. Emergent findings suggest that drama students employ contextual, social and individual learning filters to assess the usefulness of teacher feedback. In the highly interactive and relational drama classroom, social filters can induce or hinder the existence of dialogic feedback. This can subsequently influence the drama students' perspectives of the usefulness of teacher feedback. This article draws on the student voice to describe these social filters and suggests how drama teachers may culture opportunities for drama students to engage with dialogic and useful teacher feedback.